DASAR PERTIMBANGAN PENYIDIK DALAM MENERAPKAN DISKRESI KEPOLISIAN TERHADAP TINDAK PIDANA LALU LINTAS - Mardiyati, Siti; Hariyadi, Wicaksono Putra (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2023)
Investigators exercise discretion to help resolve a traffic violation case where the suspect did so because of negligence that caused injury to others. Weird problems arise as a result of this discretionary act. On the one hand, this discretionary act involves the application of criminal law carried out in accordance with its own policies to make rigid laws effective. All parties have an opportunity to know their position as a legal consequence of the choice of investigators in a traffic crime case. The party committing the violation will compensate the victim for material damage and medical costs. The increased knowledge of discretion by an investigator that is not based on the rule of law means that it is against the law